2018
DOI: 10.2967/jnumed.118.208215
|View full text |Cite
|
Sign up to set email alerts
|

Brain Imaging of Alzheimer Dementia Patients and Elderly Controls with 18F-MK-6240, a PET Tracer Targeting Neurofibrillary Tangles

Abstract: F-MK-6240 is a highly selective, subnanomolar-affinity Positron Emission Tomography (PET) tracer for imaging neurofibrillary tangles (NFTs). Plasma kinetics, brain uptake, and preliminary quantitative analysis of F-MK-6240 in healthy elderly subjects (HE), subjects with clinically probable Alzheimer disease (AD), and amnestic mild cognitive impairment (MCI) were characterized in a first-in-human study. Dynamic PET scans of up to 150 min were performed in 4 cognitively normal HE, 4 AD and 2 MCI subjects, after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 22 publications
5
74
2
Order By: Relevance
“…Preclinical binding analysis also has suggested lower binding affinity of these second-generation tracers to MAO-A and MAO-B, than the binding affinity of the first-generation tracers such as 18 F-AV1451 and 18 F-THK5351. A recent first-in-human study showed no detectable signal in the basal ganglia and brainstem, suggesting high binding selectivity of these tracers to tau deposition in patients with AD ( Villemagne, 2017 ; Lohith et al, 2018 ; Wong et al, 2018 ). Further validation studies are required to confirm the binding selectivity of these tracers.…”
Section: Development Of Tau Pet Tracersmentioning
confidence: 96%
“…Preclinical binding analysis also has suggested lower binding affinity of these second-generation tracers to MAO-A and MAO-B, than the binding affinity of the first-generation tracers such as 18 F-AV1451 and 18 F-THK5351. A recent first-in-human study showed no detectable signal in the basal ganglia and brainstem, suggesting high binding selectivity of these tracers to tau deposition in patients with AD ( Villemagne, 2017 ; Lohith et al, 2018 ; Wong et al, 2018 ). Further validation studies are required to confirm the binding selectivity of these tracers.…”
Section: Development Of Tau Pet Tracersmentioning
confidence: 96%
“…The limited in vivo data reported for other new-generation tau tracers showed similar results to our study: [ 18 F]-MK6240, [ 18 F]RO-948, and [ 18 F]-PI6260 showed elevated signals in temporal areas and more broadly throughout the cortex in AD patients compared to NC subjects. The SUVRs in temporal lobe of AD/MCI patients were 1.64 (±0.72) with [ 18 F]-MK6240 [MMSE = 18.8 (±6.9), Cohen d = 1.3) ( Lohith et al, 2019 ), 2.75 (±1.40) with [ 18 F]RO-948 (inferior temporal lobe, MMSE = 20.8 (±2.7), Cohen d = 1.6] ( Wong et al, 2018 ), and 1.80 (±0.40) with [ 18 F]-PI2620 [inferior temporal, MMSE = 20.4 (±6.3), Cohen d = 2.4] ( Mueller et al, 2019 ). Our findings of [ 18 F]-APN-1607 had relatively lower SUVR in the present study [temporal lobe: 1.64 (±0.50), MMSE = 17.0 (±7.6), Cohen d = 2.1] comparing to [ 18 F]RO-948 and [ 18 F]-PI2620, which might arise from the relatively rough ROI; however, the relatively high Cohen d value indicated that [ 18 F]-APN-1607 was a highly sensitive tracer for detecting tau aggregates in AD.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study of the second-generation MK6240 tracer has shown a high binding affinity for brain homogenate rich in NFTs [21,24]. Similarly, a recent in vivo pilot study by Lohith et al in AD patients showed that MK6240 binding occurred in regions rich in NFT deposits [25]; More recently, Pascoal et al reported that 18 F-MK6240 could be used to differentiate early and late disease stages of AD as well as discriminating AD from cognitively unimpaired and frontotemporal dementia [26]. In silico modelling has suggested the possibility of four theoretical binding sites on tau fibrils for MK6240 [27].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 92%